A closer look at the long-term patterns of regional income inequality in Spain: the poor stay poor (and stay together) - Daniel A. Tirado-Fabregat; Alfonso Díez-Minguela; Julio Martínez-Galarraga (European Historical Economics Society (EHES), 2015)
This paper explores regional (NUTS3) income inequality in Spain, 1860-2010. Using a novel dataset spanning 150 years, we analyse the evolution of inequality in regional per-capita GDP. To do this, we follow the growth literature and use spatial exploratory tools. Our aim is to understand not only the long-term evolution as regards convergence or dispersion, but also aspects related to income distribution, i.e. modality, mobility and spatial clustering. We therefore use tools such as kernel density estimates, boxplots, transition probability matrices, Shorrocks indices, Kendall's !, Moran's I and LISA maps. The main finding is that there were two clearly distinguishable periods in the economic development process. First, there was an upswing in regional inequality accompanied by a certain mobility between 1860 and 1930. This was followed by a period of regional convergence lasting until the 1980's, in which mobility in income class or rank was rather low. As a result, spatial clustering became more significant and income distribution was transformed. Decreasing regional inequality was thus accompanied by a geographical concentration of the richest and poorest regions. While wealthy Spain was located in the north-east, poor Spain was in the south, particularly the south-west. Mobility has also been virtually non-existent in recent decades. All in all, the study shows the importance of history in the shaping of Spain's regional income distribution.
Keywords: C21; O18; R0; N64; F14; 330; Regional inequality; Spain; Regional growth; Economic history